Self-effectiveness and perception of barriers and benefits of physical activity in costa rican university students - Ortega Muñoz, Angélica (2021)
According to Health Promotion Theory, factors such as self-effectiveness and the perception of benefits and barriers might be impacting physical activity. Since this phenomenon has been scarcely researched among nursing students, the purpose of this study has been to determine the relationship between self-effectiveness and perceived benefits and barriers of physical activity among nursing students at Universidad de Costa Rica. This research is a correlational, descriptive group case study. The sample was made up by 42 second-year students of the School of Nursing. The instruments used were the Scale of Benefits/Barriers for Exercise and the Self-Effectiveness Scale for Physical Activity. Data analysis was carried out through descriptive statistics and Pearson’s correlation. The most outstanding result was that walking showed higher self-effectiveness, followed by daily life activities and finally scheduled physical exercise. The student community identifies the benefits of physical activities more easily than the barriers. An association exists between total self-effectiveness for physical activity and the perception of benefits of exercise and self-effectiveness for scheduled exercise and the barriers of exercise. Efforts must be made in enhancing the benefits of physical activity, as well as in creating interventions that will help nursing students to overcome barriers by strengthening self-effectiveness for physical activity, regardless of its intensity.